A new species of Phanaeus Macleay (Coleoptera: Scarabaeidae: Scarabaeinae: Phanaeini) from Oaxaca, Mexico - Edmonds, W. D. (Zootaxa, 2006)
Phanaeus zapotecus Edmonds, new species, is described. This species occurs in the vicinity of Sola de Vega in the Sierra Madre del Sur of Oaxaca (Mexico), where it was collected from mushrooms in pine-oak forest. It is illustrated and compared with the closely related Mexican species Phanaeus endymion Harold and Phanaeus halffterorum Edmonds.Resumen: Se describe Phanaeus zapotecus Edmonds, especie nueva, especie micetófaga que habita en los bosques pino-encino de la Sierra Madre del Sur en los alrededores de Sola de Vega, Oaxaca (México). Se compara con sus parientes, las especies mexicanas Phanaeus endymion Harold y Phanaeus halffterorum Edmonds.